Case Report: Acute cerebral infarction as the initial manifestation of malignant tumors with trousseau syndrome in the elderly - Li, Chen; Fan, Miao; He, Wen; Gong, Yingying; Su, Lei (Frontiers in Oncology, 2023)
Both acute cerebral infarction and malignant tumors are prevalent in the elderly. However, acute cerebral infarction is rarely present as the first clinical manifestation of malignant tumors. By searching the Picture Archiving and Communication System from 2010 to 2022 and the medical record database from 2003 to 2022, we found three cases of Trousseau syndrome, one male and two females with an average age of 69.3±3.2 years, presenting with acute cerebral infarction. Two patients denied having hypertension, diabetes, and coronary heart disease. The average value of the D-dimer was 17.83±12.39 mg/L (normal range, 0 to 0.55 mg/L). Magnetic resonance imaging (MRI) of the brain showed scattered and multiple small infarcts in the watershed area.The sites of infarction were not those that are typically caused by vascular atherosclerosis. One of the females was diagnosed with pancreatic cancer (T2N2M1, stage Ⅳ), the male was diagnosed with gastric cancer (T4N3M1, stage IV), and the other female was diagnosed with lung adenocarcinoma (rTxN3M1b, stage IV). The patient with pancreatic cancer underwent a comprehensive geriatric assessment, which revealed that she had a disability, dementia, malnutrition, short life expectancy, and high chemotherapy risk. Ultimately, the patient opted for conservative care, and 3 months after being discharged, she passed away from an acute upper gastrointestinal hemorrhage. Elderly patients with unexplained D-dimer elevation, multiple cerebral vascular lesions detected on MRI, and an absence of typical stroke risk factors need to be monitored for Trousseau syndrome. To screen for cancer, tumor markers and related imaging should be performed first. Trousseau syndrome is primarily treated with chemotherapy, radiotherapy and anticoagulant therapy. The risk of bleeding should be assessed carefully when using anticoagulant therapy in the elderly.Comprehensive geriatric assessment can assist in weighing the benefits and side effects of cancer treatment, making correct medical choices, and improving patients' quality of life.